(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Choorna Kalpana, a fine powder derived from completely dry drugs, is a fundamental preparation in Ayurveda. Recognized for its stability and ease of absorption, Choorna is used independently to treat various diseases, as an adjuvant with other medicines, and in secondary preparations like Avaleha (medicated semisolid preparation), Vati (tablets), and Sneha Kalpana (oil and ghee preparations). The preparation involves meticulous processes of washing, drying, pounding, and sieving drugs to ensure homogeneity. Modern practices in Choorna Kalpana incorporate size reduction techniques such as cutting, compression, impact, and attrition, which enhance its efficiency and therapeutic potential. Factors influencing size reduction, including hardness, toughness, abrasiveness, stickiness, softening temperature, and moisture content, are critical for achieving desired particle sizes. Size separation and mixing techniques are also essential in ensuring the uniformity and efficacy of Choorna. This paper explores the traditional and modern methodologies of Choorna preparation, highlighting its significance in Ayurvedic medicine.